Competence ofSanitation-Hygiene of Students in Food Processing and Presentation in the Vocational High School with Catering Expertise in Bali - Luh Masdarini (Universitas Negeri Malang, 2014)
Kompetensi Higiene-Sanitasi Siswa dalam Pengolahan dan Penyajian Makanan di SMK Bidang Keahlian Tata Boga di Bali Abstract: The aim of research to uncover and describe the knowledge, attitudes, and performance of sanitary-hygiene of students in the processing and presentation of the food at the Vocational High School with Catering Expertise in Bali. This research uses descriptive quantitative research design and the research subjects students is the Vocational High School with Catering Expertise in Bali which amounts to 198 students. The research instrument used is a knowledge test, questionnaire, and observation sheet. Furthermore, the data were analyzed with descriptive technique using a percentage formula. The results showed that: (1) understanding of hygiene-sanitation student in the processing and presentation of the food at the Vocational Expertise Expertise in Bali Catering 82.89% which are very good; (2) The attitude of the students in the hygiene-sanitary processing and presentation of the food at the Vocational Expertise in Bali Catering 84.36% which are very good; (3) The performance of students in the hygiene-sanitary processing and presentation of the food at the Vocational Expertise in Bali Catering 90.20% which are very good. Key Words: comprehension, attitude, performance, principles of hygiene-sanitation, vocational, processing and presentation of food Abstrak: Tujuan penelitian untuk mengungkap dan mendeskripsikan pemahaman, sikap, dan unjuk kerja higiene-sanitasi siswa dalam pengolahan dan penyajian makanan di SMK Bidang Keahlian Tata Boga di Bali. Penelitian ini menggunakan rancangan penelitian deskriptif kuantitatif dengan subjek penelitian siswa di SMK Bidang Keahlian Tata Boga di Bali yang berjumlah 198 orang. Instrumen penelitian yang digunakan adalah tes pengetahuan, angket, dan lembar observasi. Selanjutnya data dianalisis dengan teknik deskriptif dengan menggunakan formula persentase. Hasil penelitian menunjukkan bahwa: (1) pemahaman higiene-sanitasi siswa dalam pengolahan dan penyajian makanan di SMK Bidang Keahlian Keahlian Tata Boga di Bali 82,89% termasuk kategori sangat baik; (2) Sikap higiene-sanitasi siswa dalam pengolahan dan penyajian makanan di SMK Bidang Keahlian Tata Boga di Bali 84,36% termasuk kategori sangat baik; (3) Unjuk kerja higiene-sanitasi siswa dalam pengolahan dan penyajian makanan di SMK Bidang Keahlian Tata Boga di Bali 90,20% termasuk kategori sangat baik.  Kata kunci: pemahaman, sikap, unjuk kerja, prinsip-prinsip higiene-sanitasi, SMK, pengolahan dan penyajian makanan